Bilateral One-Stage Revision of Infected Total Hip Arthroplasties: Report of Two Cases and Management of Antibiotic Therapy - Thomas Pommepuy; Adrien Lons; Kevin Benad; Eric Beltrand; Eric Senneville; Henri Migaud (Case Reports in Orthopedics)
Recommendations for the management of chronic and bilateral total hip arthroplasty (THA) infection are lacking. However, this type of infection involves medical problems concerning the management of the antibiotic therapy. We report two cases of such infections operated as one-stage revision. For each case, both hips were infected with the same bacteria (Staphylococcus caprae for one patient and methicillin-sensitive Staphylococcus aureus for the other). The probabilistic antibiotic treatment started during the first side (after harvesting intraoperative samples) did not prevent the culture of the bacteriologic harvested during the intervention of the second side. Cultures were positive for the same bacteria for both sides in the two cases presented herein. After results of intraoperative cultures, patients received culture-guided antibiotic therapy for three months and were considered cured at the end of a two-year follow-up. Our results suggest one-stage bilateral change of infected THA is a viable option and that early intraoperative antibiotic, started during the first-side exchange, does not jeopardize microbiological documentation of the second side. This work brings indirect arguments, in favor of the use of prophylactic antibiotics during revision of infected THA.